A human factors analysis of missed mobilisation after discharge from intensive care: a competition for care?. (December 2021) - Gustafson, O.D.; Vollam, S.; Morgan, L.; Watkinson, P.
Abstract: Background: Patients discharged to the ward from an intensive care unit (ICU) commonly experience a reduction in mobility but few mobility interventions. Barriers and facilitators for mobilisation on acute wards after discharge from an ICU were explored. Design and methods: A human factors analysis was undertaken using the Functional Resonance Analysis Method (FRAM) as part of the Recovery Following Intensive Care Treatment (REFLECT) study. A FRAM focus group was formed from members of the ICU and ward multidisciplinary teams from two hospitals, with experience of working in six hospitals. They identified factors influencing mobilisation and the interdependency of these factors. Results: Patients requiring discharge assessments or on Enhanced Recovery After Surgery (ERAS) pathways compete for priority with post-ICU patients with more urgent rehabilitation needs. Patients unable to stand and step to a chair or requiring mobilisation equipment were deemed particularly susceptible to missing mobilisation interventions. The ability to mobilise was perceived to be highly influenced by multidisciplinary staffing levels and skill mix. These factors are interdependent in facilitating or inhibiting mobilisation. Conclusions: This human factors analysis of post-ICU mobilisation highlighted several influencing factors and demonstrated their interdependency. Future interventions should focus on mitigating competing priorities to ensure regular mobilisation, target patients unable to stand and step to a chair on discharge from ICU and create robust processes to ensure suitable equipment availability. Trial registration number: ISRCTN14658054